The Practice Extent of the Islamic Education Teachers in Developing their Students’ Self-Learning Skills in Busra Directorate - & Khaled Al-Suodi; Nail Al-Hajaya (My University, 2013)
The study aimed at investigating the practice extent of the Islamic education teachers in developing their students’ self-learning skills during the classroom teaching. In order to achieve the aims of this study, the researcher developed an observant tool which included (17) classroom activities. The researcher checked its validity and its reliability. The study was applied on a sample of (35) Islamic education teachers from Busra district Directorate of education in Jordan for the scholastic year 2010/2011. The study findings were: the practice extent of the Islamic education teachers to develop the self-learning skills of their students during classroom teaching was medium. and there were statistical differences (α≤ 0.05) attributed  to the variables: gender, teaching experience, and the scientific degree. The study recommended that is it necessary to incorporate the self-learning skills in teachers training program and to be incorporated in the classroom visit form.

هدفت هذه الدراسة إلى تعرف درجة ممارسة معلمي التربية الإسلامية لتنمية مهارات التعلم الذاتي لدى طلبتهم أثناء التدريس الصفي، ولتحقيق هدف الدراسة قام الباحثان بتطوير بطاقة ملاحظة اشتملت على (17) إجراء صفياً، تم التأكد من صدقها وثباتها، وقد تم تطبيقها على عينة من معلمي التربية الإسلامية وعددهم (35) معلماً ومعلمة من مديرية التربية والتعليم في لواء بصيرا للعام الدراسي 2010-2011م. ومن أبرز النتائج التي أسفرت عنها الدراسة: أن درجة ممارسة معلمي التربية الإسلامية لتنمية مهارات التعلم الذاتي لدى طلبتهم أثناء التدريس الصفي جاءت متوسطة، كما أظهرت الدراسة عدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة ( 0.05 ≥ α) تعزى لمتغيرات الجنس، والخبرة، والمؤهل العلمي حول درجة الممارسة. وقد أوصت الدراسة بضرورة إدراج مهارات التعلم الذاتي في برامج تدريب المعلمين، وأن تكون متضمنة في استمارة الزيارة الصفية.
درجة ممارسة معلمي التربية الإسلامية تنمية مهارات التعلم الذاتي لدى طلبتهم أثناء التدريس الصفي في لواء بصيرا